Home from Siberia : the secret odysseys of interned American airmen in World War II - Hays, Otis, 1915- (Texas A & M University military history series ;, 1990)
Account of the experiences of American aircrew interned in Siberia during World War II and of Soviet efforts to smuggle them out of the Soviet Union.